Clinical practice guidelines for paediatric X‐linked hypophosphataemia in the era of burosumab. (15th April 2022) - Sandy, Jessica L; Simm, Peter J; Biggin, Andrew; Rodda, Christine P; Wall, Christie‐Lee; Siafarikas, Aris; Munns, Craig F
Abstract : X‐linked hypophosphataemia (XLH), the most common inherited form of rickets, is caused by a PHEX gene mutation that leads to excessive serum levels of fibroblast growth factor 23 (FGF23). This leads to clinical manifestations such as rickets, osteomalacia, pain, lower limb deformity and overall diminished quality of life. The overarching aims in the management of children with XLH are to improve quality of life by reducing overall burden of disease, optimise an individual's participation in daily activities and promote normal physical and psychological development. Burosumab, a monoclonal antibody targeting FGF23, has been shown to improve biochemistry, pain, function and radiological features of rickets in children with XLH and has transformed management of XLH around the world. Burosumab has been recently approved for clinical use in children with XLH in Australia. This manuscript outlines a clinical practice guideline for the use of burosumab in children with XLH to assist local clinicians, encourage consistency of management across Australia and suggest future directions for management and research. This guideline also strongly advocates for all patients with XLH to have multidisciplinary team involvement to ensure optimal care outcomes and highlights the need to consider other aspects of care for XLH in the era of burosumab, including transition to adult care and the effective coordination of care between local health‐care providers and specialist services.